Stock Price Behavior and Trading - Seelenfreund, Alan; Parker, George G. C.; Horne, James C. Van (Journal of Financial and Quantitative Analysis, 1968)
Alan Seelenfreund, George G. C. Parker, James C. Van Horne, Stock Price Behavior and Trading, The Journal of Financial and Quantitative Analysis, Vol. 3, No. 3, Special Issue: Random Walk Hypothesis (Sep., 1968), pp. 263-281